Food security and its determinants among rural households in Gambella region, Ethiopia - Amanuel Kussia Guyalo (Cogent Economics & Finance)
The aim of the research is to analyze demographic, socioeconomic, environmental, and institutional factors affecting the food security status of rural households in Gambella region. To attain the aim, cross-sectional data were gathered from 476 respondents drawn through a systematic random sampling strategy. Data were collected using an interview schedule questionnaire. A multiple regression model was used to identify the factors that affect the food security status of households, while principal component analysis was used to construct food security index. The findings showed that most rural households (51.1%) experienced food insecurity in nearly every dimension of food security. Regression results indicated that gender, marital status, educational level, farming system, farmland size, livestock holding, wealth status, access to credit, improved seed utilization, and social capital positively affect households’ food security status, whereas family size, commercial farming, market distance, and natural shocks negatively influence food security. The results offer important insights into how demographic, socioeconomic, institutional, and environmental factors shape households food security by examining all four dimensions of food security. Therefore, in order to improve rural households' food security, concerned regional development actors should improve households’ access to agricultural technologies and financial services, build their capacity, and expand their livelihood opportunities.